DEVELOPMENT AND RESEARCH OF A NOVEL DNC SYSTEM FOR REMOTE MONITORING OF THE MACHINE TOOLS WITH FANUC NC SYSTEM - YAO Peng; LI NanNan; CAO ZhiJun; LI HeLin; XING JunWei; LIU GuoNing (Jixie qiangdu)
A novel DNC（distributed numerical control） system,which is used to remotely monitor CNC machine tools of FANUC NC system as well as inspection equipment or devices,has been developed based on Socket communication and multithread technology by using SQL Server database and.NET platform.This DNC system can collect the real time information of CNC machines and inspection equipment or devices,and has the functions like the machine state monitoring,data integration and management,performance analysis,fault remote diagnosis,workshop production management,and product quality management and control.In this way,the data integrity and integration has been realized.The architecture of the system is presented and the approaches to the realization of the function modules are elaborated.The data flow,data interpretation and alarm monitoring mechanism are also discussed.This system has been applied in manufacturing plants and performs well.